FT-IR study of the kidney tissue - Chandra Prasad Khatiwada (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
The present study was designed to evaluate the FTIR spectra of the aluminum exposed kidney tissues and recovered by chelating agents DFO and DFP then showed significant alteration on the major biochemical constituents such as lipids, proteins and glycogen at molecular level. The significant increased in the peak area of glycogen from 0.006±0.001 to 0.187±0.032 may be the interruption of aluminium in the calcium metabolism and the reduced level of calcium. The peak area value of amide A significantly decreased from control to aluminium. Amide I and amide II peak area values also decreased from 1.690±0.133 to 0.811±0.192 and 1.158±0.050 to 0.489±0.047 but treated with DFP and DFO+DFP significantly improved. This result suggests an alteration in the protein profile.